Phenotypic Performance and The Characterization of Growth Hormone (GH|AluI) in Bangkok Chicken Breed - M. Hari Setia Budi; Depison - Depison; Gushairiyanto Gushairiyanto (Faculty of Animal Science, Universitas Brawijaya, 2023)
This study aimed to determine Bangkok chicken’s phenotypic characteristics and growth hormone genes using the PCR-RFLP method. The samples used were 50 Bangkok chickens. Research in the field is taking phenotypic traits data. Research in the laboratory is carried out by DNA isolation, amplification, and restriction. This study showed that DOC weight, body weight, and bodyweight gain of DOC-1 month, 1-2 months, 2-3 months of Bangkok chickens were significantly different (P <0.05) higher than female Bangkok chickens. The results of the molecular analysis of DNA isolation were precise, then the amplification of the GH gene fragment with a product length of 997 bp and restriction obtained a ++ genotype. Allele frequencies and genotypes obtained in the Bangkok chicken GH|AluI genes are monomorphic. Conclusion: the phenotypic characteristics of the average body weight, the body weight gain of male Bangkok chicken was higher than that of female. Allele frequencies and genotypes of Bangkok chicken are monomorphic.